Leveraging Digital Innovation to Enhance MGNREGA’s Impact on Rural Empowerment - B. Jayakumar; S. Prabakar (International Journal of Computational and Experimental Science and Engineering, 2025)
This study examines how digital innovations have affected the Mahatma Gandhi National Rural Employment Guarantee Scheme (MGNREGS), with a particular emphasis on Aadhaar-linked payments (ALP) and Direct Benefit Transfers (DBT). These technical advancements, which were first introduced in 2015 as part of the Jan Dhan, Aadhaar, and Mobile (JAM) project, were intended to improve efficiency, inclusion, and transparency by streamlining salary disbursement and reducing delays. This study evaluates the efficacy of digital interventions in enhancing program delivery by examining secondary data sources, such as government reports, scholarly literature, Management Information System (MIS) data, and Geographic Information System (GIS) analytics. GIS has also improved resource mapping, enabled targeted employment creation, tracked the quality of assets, and encouraged sustainable rural development. Notwithstanding these achievements, the research points out important areas that need focus, such improving digital literacy, building infrastructure, and implementing data security measures. Policymakers may learn a lot from this study on how to use digital governance to maximise rural employment initiatives and reduce poverty by empowering people with technology